Answer:
f(-4) = 39
Explanation:
4
x
2
−
4
x
3
+
x
4
+
3
+
7
Please write this all on one line: y = 4x^2 - 4x^3 + x^4 + 3 + 7x, and not vertically (as you have done). Note how I have used " ^ " to denote exponentiation.
We need to re arrange these terms in descending order by power of x:
y = 4x^2 - 4x^3 + x^4 + 3 + 7x => y = x^4 - 4x^3 + 4x^2 + 7x + 3.
We are to evaluate this polynomial for x = -4. Either replace each instance of x by -4 or use synthetic division (the remainder is the value of the polynomial at the given x-value.
At x = -4, we have y = (-4)^4 - 4(-4)^3 + 4(-4)^2 + 7(-4) + 3, or
y = 256 - 256 + 64 - 28 + 3, or 39 (answer)